Impact of TCP congestion control on bufferbloat in cellular networks - Stefan Alfredsson; Giacomo Del Giudice; Johan Garcia; Anna Brunstrom; Luca De Cicco; Saverio Mascolo (2013 IEEE 14th International Symposium on "A World of Wireless, Mobile and Multimedia Networks" (WoWMoM), 2013)
The existence of excessively large and too filled network buffers, known as bufferbloat, has recently gained attention as a major performance problem for delay-sensitive applications. One important network scenario where bufferbloat may occur is cellular networks. This paper investigates the interaction between TCP congestion control and buffering in cellular networks. Extensive measurements have been performed in commercial 3G, 3.5G and 4G cellular networks, with a mix of long and short TCP flows using the CUBIC, NewReno and Westwood+ congestion control algorithms. The results show that the completion times of short flows increase significantly when concurrent long flow traffic is introduced. This is caused by increased buffer occupancy from the long flows. In addition, for 3G and 3.5G the completion times are shown to depend significantly on the congestion control algorithms used for the background flows, with CUBIC leading to significantly larger completion times.
Keywords: Measurement